Learning cultures in retail : apprenticeship, identity and emotional work in England and Germany - Brockmann, Michaela [Verfasser] (My University, 2013)
"The paper is based on a study of apprentices in retail and motor vehicle maintenance in England and Germany, exploring their perceptions of themselves as learners over time and in particular learning environments. The study combines biographical interviews with participant observation in colleges and workplaces. The paper examines the concept of emotion work in the context of retail apprenticeships. It explores the extent to which the skill of emotion management is developed through apprenticeship programmes and the meaning young people attach to it in the context of their individual biographies. Comparing the German dual system with the minimalist approach of an English supermarket, it concludes that emotion work may be part of an occupational competence offering positive means for identification as a critical resource for young people’s negotiation of identity. The findings challenge existing conceptualisations of emotional labour and have important implications for the provision of apprenticeships in the service sector." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; T 4.2 Psychologie; G 1.3.3 Bildungs- & Erwerbsbiografien; G 1.2.4.2.1 Handel, Instandhaltung, Reparatur von Kfz und Gebrauchsgütern; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsausbildung; Berufliche Identität; Emotionalität; Biografieforschung; Einzelhandel; Internationaler Vergleich; Bundesrepublik Deutschland; England